Synergistic Anticancer Activities of Natural Substances in Human Hepatocellular Carcinoma - Akiko Kojima-Yuasa; Xuedan Huang; Isao Matsui-Yuasa (Diseases, 2015)
Hepatocellular carcinoma (HCC) is highly resistant to currently available chemotherapeutic agents. The clinical outcome of HCC treatment remains unsatisfactory. Therefore, new effective and well-tolerated therapy strategies are needed. Natural products are excellent sources for the development of new medications for disease treatment. Recently, we and other researchers have suggested that the combined effect of natural products may improve the effect of chemotherapy treatments against the proliferation of cancer cells. In addition, many combination treatments with natural products augmented intracellular reactive oxygen species (ROS). In this review we will demonstrate the synergistic anticancer effects of a combination of natural products with chemotherapeutic agents or natural products against human HCC and provide new insight into the development of novel combination therapies against HCC.